Effect of maturity stage on the nutritive value of native grass hay - M.R. Rao; L.H. Harbers; A.M. Latschar; E.F. Smith (Kansas Agricultural Experiment Station Research Reports, 1972)
The evaluation of pastures by esophageally fistulated steers requires artificial rumen techniques to determine digestibilities of grasses. To develop a regression curve between data obtained by an artificial rumen and those from a grazing animal, we conducted a series of metabolism studies and artificial rumen trials using native prairie hay from the Flint Hill area cut at three maturity stages.
Keywords: Cattlemen' s Day; 1972; Report of progress (Kansas State University. Agricultural Experiment Station); 557; Beef; Grass Hay; Maturity